Clinical dimensions of fibromyalgia symptoms and development of a combined index of severity: the CODI index. - Cuesta-Vargas A; Luciano JV; Peñarrubia-María MT; García-Campayo J; Fernández-Vergel R; Arroyo-Morales M; Serrano-Blanco A; Cuesta-Vargas, Antonio; Luciano, Juan V; Peñarrubia-María, Maria Teresa; García-Campayo, Javier; Fernández-Vergel, Rita; et al. (Quality of Life Research, 2013)
Background: Although a large body of work indicates that fibromyalgia (FM) is not a discrete entity, few studies have attempted to classify the heterogeneity of FM symptoms. The objectives of the present study were to confirm the existence of two latent dimensions underlying FM symptoms (Core-FM symptoms and Distress) by means of factor analysis techniques, and to develop and validate a new combined index of symptom severity (the CODI).Methods: We analyzed and combined the baseline scores on six visual analog scales of the FIQ (pain, general fatigue, morning fatigue, stiffness, anxiety, and depression) and on the STAI-T (trait anxiety) of 216 Spanish patients diagnosed with FM (97.7% women) who were participating in a randomized, controlled trial.Results: The principal component analysis indicated the presence of two correlated factors (labeled as Core-FM symptoms and Distress) that explained 64% of total variance. The subsequent confirmatory factor analysis yielded more empirical support for the two-factor model than the one-factor model (all items loading on one latent dimension). The two factors possessed adequate internal consistency and construct validity given the pattern of significant correlations with the Euroqol items. The Core-FM dimension had a stronger relationship with mobility, self-care, usual activities, and pain/discomfort than with anxiety/depression, whereas the Distress dimension showed the opposite pattern. Finally, summing the standardized scores of the two dimensions, a new combined index of symptom severity (the CODI) was developed.Conclusion: The clinical implications and utility of the CODI are discussed in relation to previous research on FM.